2023
DOI: 10.20944/preprints202303.0057.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nutrition and Physical Activity as Modulators of Osteosarcopenic Adiposity: A Scoping Review and Recommendations for Future Research

Abstract: Osteosarcopenic adiposity (OSA) syndrome denotes the confluence of bone, muscle, and adipose tissue deterioration. Being a complex entity, numerous uncertainties about OSA still exist, despite the extensive research on the topic. Our objectives were to evaluate human studies addressing dietary intake/nutritional status, and the quantity/types of physical activity related to OSA. The search in PubMed, Scopus, and Web of Science databases was conducted to examine relevant articles published from inception to the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
(211 reference statements)
0
2
0
Order By: Relevance
“…In addition, a link between infectious diseases and the development of complex conditions related to body composition has been suggested [14]. Furthermore, the lack of new original data on the potential cellular and molecular mechanisms involved in the events leading to the skeletal alterations in subjects with sarcopenic obesity, recent interesting reviews highlight the main points of future research in this field [15 Since the concomitant presence of obesity, sarcopenia, and osteoporosis represents a dreadful trio potentially occurring in postmenopausal women and individuals of advanced age, as each of these conditions is related with adverse outcomes in terms of morbidity, quality of life, and mortality [16], recent works have tried to identify clinical potential early biomarkers and factors further involved in OSO development [17]. Interestingly, a few studies have suggested that high serum ferritin levels are strongly linked to metabolic syndrome, obesity, impaired muscle quality, and sarcopenia [18].…”
Section: Interplay Of Adipose Tissue Skeletal Muscle and Bonesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a link between infectious diseases and the development of complex conditions related to body composition has been suggested [14]. Furthermore, the lack of new original data on the potential cellular and molecular mechanisms involved in the events leading to the skeletal alterations in subjects with sarcopenic obesity, recent interesting reviews highlight the main points of future research in this field [15 Since the concomitant presence of obesity, sarcopenia, and osteoporosis represents a dreadful trio potentially occurring in postmenopausal women and individuals of advanced age, as each of these conditions is related with adverse outcomes in terms of morbidity, quality of life, and mortality [16], recent works have tried to identify clinical potential early biomarkers and factors further involved in OSO development [17]. Interestingly, a few studies have suggested that high serum ferritin levels are strongly linked to metabolic syndrome, obesity, impaired muscle quality, and sarcopenia [18].…”
Section: Interplay Of Adipose Tissue Skeletal Muscle and Bonesmentioning
confidence: 99%
“…Since the concomitant presence of obesity, sarcopenia, and osteoporosis represents a dreadful trio potentially occurring in postmenopausal women and individuals of advanced age, as each of these conditions is related with adverse outcomes in terms of morbidity, quality of life, and mortality [16], recent works have tried to identify clinical potential early biomarkers and factors further involved in OSO development [17]. Interestingly, a few studies have suggested that high serum ferritin levels are strongly linked to metabolic syndrome, obesity, impaired muscle quality, and sarcopenia [18].…”
Section: Biomarkersmentioning
confidence: 99%